School-Aged Bullying History, Post-Traumatic Stress Disorder (PTSD), and Depressive Symptoms: A Study of University Students in Malaysia - Pauzi, Noraskin (Animo Repository, 2023)
The present study investigated school-aged bullying history among university students in Sarawak and its relationship with depressive and PTSD symptoms and types of bullying. A total of 499 university students (Mage = 19.52, SD = 1.58) participated in this cross-sectional study, of which 72.1% (n = 360) were females and 27.9% (n = 139) were males. Results indicated a high prevalence of bullying history, 38.1% (n = 190); 21.4% (n = 107) identified as victims, 9.4% (n = 47) bullies (perpetrators), and 7.2% (n = 36) are bully–victims (being both perpetrators and victims). Participants with a bullying history scored significantly higher in depressive and PTSD symptoms. Based on the present findings, school-aged bullying history is one of the potentially traumatic events experienced by university students. The present findings contribute to the knowledge of the risk of developing depressive and PTSD symptoms. Prevention and intervention plans are needed to prevent school bullying from getting worse. Finally, it should be cautioned that this study adopted a convenient sample, and thus, the results cannot be generalized to other university students.